The Position of the Deed and the Responsibility of the Notary for Deeds Read Outside the Working Area of the Notary in Realizing Legal Certainty and Justice - Achmad Kotyi, Julius; Djajaputra, Gunawan (Pusat Publikasi Nusantara, 2023)
Notaries such as Public Officials who make authentic deeds are prohibited from reading deeds outside their work area. The problem is that there are still many Notaries who read deeds outside their work area which results in changes in the status of the deeds they make. The method used in this research is normative juridical by conducting research through the literature on secondary data, especially primary legal materials in the form of statutory regulations and secondary legal materials in the form of books and articles or journals, using the theory of responsibility and Law Enforcement. The results of the research show that to date Notaries who read deeds outside their area of office have violated the law and the Notary's code of ethics, therefore Notaries can be held accountable by parties who have been harmed by reading deeds carried out outside their area. position of Notary, it can be concluded that law enforcement against Notaries who read deeds outside their area of office is not optimal. Therefore, in terms of proof, the deed he made is no longer authentic, but a private deed.